Designing an E-Booklet to Promote Palembang Harum as Culinary Tourism - Heriyanto (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2024)
This research aims to design an e-booklet about Palembang's traditional cakes sold by Palembang Harum to support Palembang's culinary tourism. The problem in this paper is how to design E-Booklet as promotion media of Palembang Harum as a culinary tourism in Palembang. The purpose of this paper is to design E-Booklet as promotion media of Palembang Harum as a culinary tourism in Palembang. The writer used the research and development (R&D) method. This method has 3 steps, namely preliminary studies, model development, and final product testing. The writer relates these steps to the 7 stages of manuscript development. Based on the findings, the writer created a 46-page e-booklet containing Palembang Harum as a culinary tourism in Palembang. It is concluded that there are 7 steps in designing an e-booklet, namely: background research and investigation, concept, pitching, treatment, first draft, revision, and final draft.